FUZZY LOGIC CONTROL FOR MULTI-MACHINE POWER SYSTEM - BOUCHIBA, BOUSMAHA; ROUINA, ABDELHAFID (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
Stability enhancement is of great importance in power system design. Excitation control and static var compensator (SVC) play important roles in stability enhancement of power system. In this paper, an indirect adaptive fuzzy excitation control is proposed to enhance transient stability for the power system, which based on input-output linearization technique. A three-bus system, which contains a generator and static var compensator (SVC) is considered in this paper, the SVC is located at the midpoint of the transmission lines. Simulation results show that the proposed controller can enhance the transient stability of the power system under a large sudden fault, which may occur nearly at the generator bus terminal.